353 Microbiome analysis in elite sport. (3rd March 2020) - Needleman, Ian; Klein, Brian; Hendrickson, Jared; Davrandi, Mehmet; Gallagher, Julie; Ashley, Paul; Spratt, David
Abstract : Background: There is increasing interest in the microbiome in performance and prevention of illness. Objective: To investigate characteristics of oral and gut microbiomes in elite sport. Design: Metagenomic sequencing performed on stool and saliva samples at baseline and three months. Taxanomic identification of the DNA sequence data generated on the Illumina sequencing platform, followed by unsupervised Principle Component Analyses (PCA). UCL Research Ethics Committee ID Number: 6388/002. Setting: 1: A GB Olympic team, n=18; 2: English premiership rubgy team, n=18; 3: Healthy volunteers (non-athletes) n=28. Participants: Aged ≥18 years, able to understand consent process, for health controls body mass index18 to 30 kg/m2. Assessment of risk factors: Oral health, BMI, use of antibiotics. Outcome measurements: Unsupervised PCA. Results: Two distinct clusters emerged, one of athletes and one of non-athletes. Specific species-level signatures distiguishing the two clusters as well as each cohort were identified, including Fusicatenibacter sacchrivorans enriched in athlete samples relative to non-athlete controls, Slackia isoflavoniconvertans enriched in rugby relative to both Olympic athletes and non-athletes, and Klebsiella pnemoniae enriched in Olympic cohort relative to both rubgy and non-athletes (all P<0.005). For saliva PCA analyses, no distinct clusters emerged between the two athlete cohorts or timepoints. However, specific species-level signatures distiguishing the groups were indentified, including multiple Neisseria spp . being elevated in rubgy relative to Olympic athetes at both timepoints, Prevotella histicola being elevated in Olympic athletes relative to rubgy at both timepoints, and Bifidobacterium longum being almost exclusively detected in the Olympic cohort but not rugby. Conclusions: Marked differences in microbiome signatures were found both between elite athletes and non-athletes and between team and individual sport cohorts. Further studies may help identify microbial factors related to optimal food conversion, performance or recovery, and prediction of illness risk.